OPTIMALISASI PRODUKSI PADA MEBEL MAHAKAM SAMARINDA - HANDOYO, AHMAD BUDI (EKONOMIA, 2013)
Ahmad Budi Handoyo , furniture production optimization Mahakam Samarinda , under the guidance of Mrs. Dra.Elfreda A. Lau , Msi and Mr. Heriyanto , SE , MM.To find furniture production optimization conducted an analysis beforehand . In connection with the problem that arises is whether the production of furniture in the furniture business in the Mahakam Samarinda were optimal profit , the author tries to analyze the production of furniture in the furniture business Mahakam Samarinda using the simplex method and linear program (Linear Programming) . In this report the authors found the hypothesis of the existing problems of